A dual-functional buformin-mimicking poly(amido amine) for efficient and safe gene delivery. (20th October 2020) - Lu, Mei; Xing, Haonan; Cheng, Lin; Liu, Hui; Lang, Lang; Yang, Tianzhi; Zhao, Xiaoyun; Xu, Hui; Ding, Pingtian
Abstract: Biguanides (i.e. metformin, phenformin and buformin) are antidiabetic drugs with potential antitumor effects. Herein, a polycationic polymer, N, N ′-bis(cystamine)acrylamide-buformin (CBA-Bu), containing multiple biodegradable disulphide bonds and buformin-mimicking side chains was synthesised. CBA-Bu was equipped with high efficiency and safety profile for gene delivery, meanwhile exhibiting potential antitumor efficacy. As a gene vector, CBA-Bu was able to condense plasmid DNA (pDNA) into nano-sized (<200 nm), positively-charged (>30 mV) uniform polyplexes that were well resistant to heparin and DNase I. Due to the reduction responsiveness of the disulphide bonds, CBA-Bu/pDNA polyplexes could release the loaded pDNA in the presence of dithiothreitol, and induce extremely low cytotoxicity in NIH/3T3 and U87 MG cells. The transfection results showed that CBA-Bu had a cellular uptake efficiency comparable to 25 kDa PEI, while a significantly higher gene expression level. Additionally, CBA-Bu had a lower IC50 value than its non-biguanide counterpart in two cancer cell lines. Furthermore, CBA-Bu could activate AMPK and inhibit mTOR pathways in U87 MG cells, a mechanism involved in the antitumor effect of biguanides. Taken together, CBA-Bu represented an advanced gene vector combining desirable gene delivery capability with potential antitumor activity, which was promising to achieve enhanced therapeutic efficacy in antitumor gene therapy.